PEMBELAJARAN PRAKTIKUM PADA PROGRAM KEAHLIAN BUSANA DI SMK DAERAH ISTIMEWA YOGYAKARTA - Flori Setiarini, Yosephine (LPMPP Universitas Negeri Yogyakarta, 2009)
Thisstudy aimed to investigate (1) the effectiveness of practicum learning at the Fashion Expertise Program in State Vocational High Schools in Yogyakarta Special Territory, and (2) the effect of teachers mastery on practicum learning materials, practicum learning methods, teachers understanding of students characteristics, and teachers competence in evaluation on the effectiveness of practicum learning. This study was a correlational ex post facto study. The sample consisted of 202 Year II students of the Fashion Expertise Program in State Vocational High Schools in Yogyakarta Special Territory, selected from a population of 425 students by the proportional random sampling technique. The data were analyzed by using the descriptive technique, partial correlation, and multiple regression at a significance level of 5%. The results of the descriptive analysis showed that the effectiveness of the practicum learning was in the good category (mean = 7.97 and maximum score = 9.22). The partial correlation analysis showed that there was a positive and significant influence of teachers mastery on practicum learning materials, practicum learning methods, teachers understanding of students characteristics, and teachers competence in evaluation on the effectiveness of practicum learning, with coefficients of, respectively, r1y (2, 3, 4) = 0.326, r2y (1, 3, 4) = 0.187, r3y (1, 2, 4) = 0.182, and r4y (1, 2, 3) = 0.163. The multiple regression analysis showed that the coefficient of the multiple correlation R was 0.553. The coefficient of determination (R2) was 30.60%, consisting of teachers mastery on practicum learning materials (7.20%), practicum learning methods (15.60%), teachers understanding of students characteristics (5.90%), and teachers competence in evaluation (1.90%).Keywords: effectiveness, practicum learning